Barb the last Berzerker. Book 1 - Abdo, Dan; Jason (Jason Linwood Patterson) (Simon & Schuster Books for Young Readers, 2021)
Barb is a Berzerker, a warrior sworn to protect the land of Bailiwick from the horrifying monsters. While fighting the notorious Witch Head, he captures the Zerks using his magical sword and Barb is the only one to escape. Barb embarks on a dangerous quest with the help of her friend, Porkchop the yeti, to stop Witch Head from taking over Bailiwick. Along the way, she encounters the bear beast, Mergoblins, the Grub of Death, and a giant named Grom.